Strengthening the Literature of Islamic Religious Education Teachers to Increase Pedagogic and Professional Competence at Teacher Working Group Islamic Religious Education Cianjur Regency - Neneng Muhibah (Global Writing Academica Researching and Publishing, 2022)
This study aims to determine the implementation of Islamic Religious Education Teacher literacy strengthening to improve pedagogic and professional competencies, analyze Islamic Religious Education Teacher literacy strengthening programs to improve pedagogic and professional competencies, analyze the increase in Islamic Religious Education Teacher pedagogic and professional competencies after strengthening Islamic Religious Education Teacher literacy, and find out the results of the Islamic Religious Education Teacher literacy strengthening program to improve pedagogical and professional competence. The research method used is an experiment with pre and post-matching control groups. The research subjects were 34 Islamic Religious Education Teacher Primary School at Teacher Working Group Islamic Religious Education Cianjur. Collecting data using tests, interviews, observations, and documentation. The data were analyzed with a quantitative approach. The results of the study are as follows. First, some Islamic Religious Education Teachers are still weak in understanding pedagogic and professional competencies. This condition is motivated by the low involvement of Islamic Religious Education teachers in the Continuing Professional Development (PKB) program. Second, the literacy program focuses on two things, namely literacy strengthening training, mentoring, and product documentation assessment. The training is carried out using a learning by doing approach. Strengthening literacy is guided by the team to produce products following the substance.